Nível de proficiência do IDEB de matemática: um Estudo comparativo entre escolas municipais e estaduais de Cascavel - Santos, Marcieli Ribeiro dos (2021)
The present research “IDEB Mathematics Proficiency Level: a Comparative Study Between Municipal and State Schools in Cascavel”, developed at Western Parana State University – UNIOESTE, Cascavel/PR campus, which takes as a line of research “Education, Social Policies and the State”, seeks the comprehension of what are the possible factors that may result in the disparity in the level of proficiency of the Basic Education Development Index (IDEB) in mathematics subject of the municipal and state schools in Cascavel, in the 5th and 9th grades of Elementary School, Initial and Final Years. This theme is relevant when considering the performance of Brazilian students in large-scale external assessments, which, despite having significantly evolved, it is still far from the ideal to be considered as a quality education. The metodology used in the present work is the comparative study, carrying out a bibliographic and documental survey seeking to understand the historical context of the implementation of the National System for the Evaluation of Basic Education (SAEB), the changes that have taken place since the implementation of large-scale assessments in the country, the implementation of goals for education with the creation of the National Education Plan (PNE), Common National Curriculum Base (BNCC) which is a guiding document for teaching that defines what learning should be worked on in public and private schools of Early Childhood Education, Elementary School and High School, in order to guarantee equity in education.